GERAKAN TANAM BUAH UNGGUL UNTUK PENYIAPAN EDU-AGROWISATA KAWASAN KAMPUS UNIVERSITAS PADJADJARAN DI KABUPATEN PANGANDARAN - Hermanto, Bambang; Sitio, Nurul Mardhiah; Thirafi, Luthfi; Kurniawati, Linda; Sahda, Rainaldi Mardiana (Universitas Padjadjaran, 2026)
Pangandaran Regency is renowned for its abundant agricultural products, as well as fisheries and livestock, including honje fruit, avocado, durian, rambutan, banana, sapodilla, and fern vegetables. With its fertile soil, Pangandaran Regency has great potential to be developed into an Edu-Agrotourism area—a program that provides hands-on experience in sustainable agriculture, livestock, and fisheries. However, until 2025, there has been no Edu-Agrotourism business initiative by local residents, the government, or the private sector. Seeing this vast untapped potential, the Padjadjaran University community service team is attempting to initiate an Edu-Agrotourism program through community empowerment activities. These activities include workshops and practical avocado and durian seedling planting on campus, within the community, and on the land of Cintaratu Village, Parigi District, Pangandaran Regency. The activities aim to equip local residents and village officials with training in planting and cultivating avocado and durian seedlings, as well as providing them with the necessary equipment to care for these plants. The results have led to growing awareness and understanding among the community and the Unpad academic community regarding Edu-Agrotourism, supported by their improved ability to care for plants as part of the Edu-Agrotourism ecosystem. This community service activity is the first step toward pioneering Edu-Agrotourism in Cintaratu Village, Pangandaran Regency, in the following year. The analysis indicates that Edu-Agrotourism in the Unpad Pangandaran campus area is worthy of further development.Kabupaten Pangandaran telah terkenal dengan hasil pertanian yang melimpah selain dari hasil perikanan dan peternakan, antara lain buah honje, alpukat, durian, rambutan, pisang, sawo, dan sayur pakis. Dengan kondisi tanah yang subur, wilayah kabupaten Pangandaran memiliki potensi besar untuk dijadikan sebagai kawasan Edu-Agrowisata, yakni kegiatan pendidikan dan agrowisata yang memberikan pengalaman langsung terkait praktik pertanian, peternakan, maupun perikanan yang berkelanjutan. Akan tetapi, hingga tahun 2025 belum ada inisiasi bisnis Edu-Agrowisata oleh warga sekitar, pemerintah, maupun pihak swasta. Melihat potensi besar yang belum termanfaatkan tersebut, tim pengabdian Universitas Padjadjaran berupaya menginisiasi program Edu-Agrowisata melalui kegiatan pemberdayaan masyarakat. Kegiatan pengabdian dilakukan dengan workshop serta praktik penanaman bibit alpukat dan durian di wilayah kampus, warga sekitar, serta di wilayah tanah desa Cintaratu, Kecamatan Parigi, Kabupaten Pangandaran. Kegiatan bertujuan untuk membekali penduduk sekitar dan perangkat desa dengan pelatihan penanaman dan teknik budidaya bibit tanaman alpukat dan durian, serta diberikan kelengkapan untuk merawat tanaman-tanaman tersebut. Hasilnya mulai tumbuh kesadaran dan pemahaman masyarakat maupun civitas Unpad mengenai Edu-Agrowisata yang didukung dengan kemampuan merawat tanaman sebagai bagian dari ekosistem Edu-Agrowisata. Kegiatan pengabdian ini merupakan langkah awal untuk merintis Edu-Agrowisata di wilayah Desa Cintaratu Kabupaten Pangandaran di tahun berikutnya. Hasil analisa menunjukkan Edu-Agrowisata di kawasan kampus Unpad Pangandaran layak memasuki tahap pengembangan lebih lanjut.